2011
DOI: 10.1590/s1517-83822011000300034
|View full text |Cite
|
Sign up to set email alerts
|

Growth and biopigment accumulation of cyanobacterium Spirulina platensis at different light intensities and temperature

Abstract: In order to find out optimum culture condition for algal growth, the effect of light irradiance and temperature on growth rate, biomass composition and pigment production of Spirulina platensis were studied in axenic batch cultures. Growth kinetics of cultures showed a wide range of temperature tolerance from 20 °C to 40 °C. Maximum growth rate, cell production with maximum accumulation of chlorophyll and phycobilliproteins were found at temperature 35 °C and 2,000 lux light intensity. But with further increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 7 publications
6
47
0
3
Order By: Relevance
“…Another factor which affects microalgae growth and cell content is light (Kumar et al 2011;Pérez-Pazos and Fernández-Izquierdo 2011). The variation in light intensity and photoperiod might influence lipid production in the microalgae cells, because lipoid production is associated with carbon content (Pérez-Pazos and Fernández-Izquierdo 2011).…”
Section: Characteristics Of Wet Market Wastewater and Slaughterhouse mentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor which affects microalgae growth and cell content is light (Kumar et al 2011;Pérez-Pazos and Fernández-Izquierdo 2011). The variation in light intensity and photoperiod might influence lipid production in the microalgae cells, because lipoid production is associated with carbon content (Pérez-Pazos and Fernández-Izquierdo 2011).…”
Section: Characteristics Of Wet Market Wastewater and Slaughterhouse mentioning
confidence: 99%
“…However, excessive light exposure can cause light prohibition in microalgae (Ren 2014). Kumar et al (2011) found that the maximum light intensity to produce carotenoid in Spirulina platensis was 3500 lx, while the highest amount of biomass was obtained at 2000 lx (0.71 g/L).…”
Section: Characteristics Of Wet Market Wastewater and Slaughterhouse mentioning
confidence: 99%
“…Also, Richardson et al (1983) reported pigment content and photosynthetic activity of microalgae cultured significantly changed due to differences in light intensities. In addition, Kumar et al (2011) reported that Spirulina platensis carotenoid content increased with increasing light. This is a form of adaptation mechanisms of microalgae for photo-protection.…”
Section: The Content Of Chlorophyll-a and Total Carotenoids Nannochlomentioning
confidence: 99%
“…In Scytonema, increasing irradiance levels gradually increases antibiotic production [87]. The increase of light intensity stimulates the secretion of polymeric substances from Arthrospira platensis [68] and improves its carotenoid content [88].…”
Section: Effects Of Temperature Irradiance and Their Interaction On mentioning
confidence: 99%